Phantoms - Chappelle, Joe; Affleck, Ben, 1972-; McGowan, Rose, 1975-; Going, Joanna; Williams, David; Koontz, Dean R. 1945- (Dean Ray); Neo Motion Pictures; Dimension Home Video (Firm); Buena Vista Home Video (Firm) (Burbank, CA : Dimension Home Video, 1998)
Five lone survivors in a devasted town must face an evil force, lying below the earth for centuries, that has resurfaced with the power to destroy human life.
Based on the novel by Dean Koontz.
Originally released as a motion picture.
Features: chapter search.
Director of photography, Richard Clabaugh ; production designers, Deborah Raymond, Dorian Vernacchio ; editor, Randolph K. Bricker ; music, David Williams.
Ben Affleck, Rose McGowan, Joanna Going, Liev Schreiber, Peter O'Toole.
MPAA rating: R.
Keywords: Koontz, Dean R. -- 1945- -- Film and video adaptations; Video recordings for hard of hearing people; Based on the book; Feature films; Horror films